The Role of Biblical Parenting In Minimizing Bad Behavior of Pastor's Children - Henny Sukmawati; Yanto Paulus Hermanto; Guntur Hari Mukti (Sekolah Tinggi Teologi Berita Hidup, 2023)
Children born as pastor’s kids often face pressures from the church environment and its surrounding; as they grow and develop, they are often expected to be good and even role models to others. It is not an easy condition to live in, and pastor’s kids often find it burdensome. Moreover, the opposite also often happens in real life. Pastor’s kids often display destructive behaviors and cause many problems. The research aims to help parents who work as pastors find solutions to the problem of bad behavior in their children. This research uses the literature study method. This research presents biblical parenting as the primary key to solving pastors' kids’ problematic behaviors. This is marked by a balance between teaching and giving examples, including maintaining a harmonious husband-wife relationship, applying biblical discipline, and giving unconditional love and acceptance.